Diversidade e estrutura genética populacional em jaboticabais nativos no sudoeste do Paraná - Salla, Vanessa Padilha (2019)
Jabotica trees (Plinia sp.) belong to the family Myrtaceae and are native to the Center-South/Southeast regions of Brazil. Its fruit has a great commercialization potential, as they are much appreciated for fresh consumption. The objective of this work was to verify the organization and distribution of genetic variability among and within six populations of jaboticabeiras (Plinia. Cf. peruviana) native to southwestern Paraná, and two populations with generations of adults and juveniles, aiming to define conservation strategies. Situ and germplasm collection for ex situ conservation. The sample consisted of a total of 190 adult individuals and 80 juvenile individuals, being collected in the cities of Vitorino (n = 30 Adul .; n = 40 Juv.), Chopinzinho (n = 40), Clevelândia (n1 = 40 Adul. ; n = 40 Juv. and n 2 = 25), Colonel Vivida (n = 30) and Pato Branco (n = 25). Samples of mature jaboticabeira leaves were collected at each site and genotyped with 10 microsatellite markers. The ten loci analyzed showed high genetic diversity for the six populations, both for adult and juvenile jabuticaba trees. For the Vitorino population, heterozygous loci were high, suggesting selection in favor of heterozygotes. Clones were detected in the populations, this suggests that the population was formed by few generating individuals (founder effect), followed by multiplication of individuals by cloning through seeds generated by apomixia. There were significant signs of genetic bottleneck for the six natural jabuticaba tree populations. Genetic differentiation between populations was significant and of intensity ranging from high to moderate (Fst = 0.176). The genetic structure of the six jaboticabeira populations showed that most of the genetic variability is within individuals. The analysis of spatial genetic structure shows that genotypes have a random distribution in populations. Juvenile individuals present similar gene pool to adults in the two populations studied. The results of this work indicate that the populations of jaboticabeiras present high genetic diversity, with high number of alleles and high heterozygosis. For in situ conservation, genetic diversity should be included within areas, with the formation of ecological corridors between nearby forest fragments containing jaboticabeira, taking into account areas of conservation importance, especially the Vitorino population, which presents a differentiation. genetics in relation to other populations. For ex situ conservation of jaboticabeira seeds should be collected from more than 50 trees by populations distant from each other for more than 50 meters, avoiding kinship between the genotypes.